Analisis Karakteristik Demografis Dan Lama Penggunaan Kosmetik Terhadap E-WOM Dan Keputusan Pembelian Merk Emina di Kota Semarang (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2022)
Cosmetics are currently a commodity that is needed by women to support their daily appearance. As a primary need for women, of course, the cosmetics industry encourages higher competition, one of which is Emina as a local cosmetic brand in Indonesia. Local brands certainly not easy to occupy the top position compared to imported brands. Thus the ability of E-Wom to influence purchasing decisions is very important by taking into account the demographic characteristics of consumers in Indonesia. This study aims to determine the effect of E-Wom on purchasing decisions with the moderation of demographic characteristics and length of use. This study used a sample of 100 respondents who live in Semarang, Central Java. This research was conducted by distributing questionnaires directly and questionnaires in the form of google forms. The analytical tool used in this research is WarpPls analysis. The results showed that E-Wom had a significant effect on purchasing decisions, the length of use of cosmetics had a significant effect as a moderator between E-Wom and purchasing decisions, demographic characteristics, namely age and income level, had no significant effect on moderating the relationship between E-Wom and purchasing decisions. Emina Cosmetics needs to consider the role of the best experiences from consumers as users of local cosmetics because with experience, consumers can provide the best information to others. This experience can be applied in the form of product and pricing strategies that are better than before. Keywords: E WOM; Demographic characteristics; prolonged use of cosmetics; buying decision